STUDENTS’ PERSPECTIVES IN STUDYING MATHEMATICS SUBJECT THROUGH E-LEARNING TOOLS AT FOUNDATION EDUCATION LEVEL - Che Haziqah Che Hussin; Nurliyana Juhan; Suriana Lasaraiya; Ayu Afiqah Nasrullah (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The aim of the study was to find out how students preferred using asynchronous and synchronous e-learning tools. Asynchronous learning occurs when there is no predetermined time for it to take place. Learners can learn whenever and wherever they want, and they can take their time to learn what they need to know. Synchronous e-learning is characterized by structured and time-bound activities delivered via web conferencing and chatting. At the Preparatory Centre for Science and Technology, Universiti Malaysia Sabah (PCST, UMS) lecturers could conduct synchronous or asynchronous due to MCO which was enforced on March 18, 2020. As a result, this study was done to examine the impact of several learning styles on foundation UMS students during the COVID-19 crisis, including synchronous and asynchronous. The quantitative data analysis of research will be presented in this study. Microsoft Excel was used for data analysis. The male and female students’ opinions were compared using an independent sample t-test. Additionally, the responses of students to various aspects of e-learning were represented using descriptive statistics. The findings found a significant difference in students’ perceptions of the efficacy of asynchronous e-learning activities. Female studentsâ€™ responses show that they found asynchronous is more effective than male students at the foundation education level. Students were found to have a greater interest in asynchronous and blended learning activities.